2022
DOI: 10.1200/jco.2022.40.16_suppl.2504
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 trial of TIM-3 inhibitor cobolimab monotherapy and in combination with PD-1 inhibitors nivolumab or dostarlimab (AMBER).

Abstract: 2504 Background: TIM-3 expressed on tumor-infiltrating T cells is associated with T-cell suppression. AMBER (NCT02817633) is evaluating cobolimab (TSR-022/GSK4069889) monotherapy and with PD-1 inhibitors in advanced solid tumors. Methods: Multi-center, open-label study conducted with the following escalation arm (Parts 1A–C primary analysis reported here): (1A) cobolimab (IV Q2W) monotherapy at 7 doses (6 weight-based [0.03–10 mg/kg] and 1 flat [1200 mg] dose); (1B) cobolimab (1 mg/kg) + nivolumab (3 mg/kg IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…A phase I/II trial (NCT02608268) evaluated MGB453 (anti-TIM3) in combination with PDR001 (anti-PD-1) in advanced solid cancers such as melanoma and NSCLC and showed excellent safety profile and preliminary antitumor activity ( 170 ). Similar encouraging results were shown by trials (NCT02817633 and NCT03680508) that evaluated TSR-022 (anti-TIM3) in combination with PD-1 inhibitors ( 171 , 172 ). In addition, a phase Ia/b trial evaluated the safety, pharmacokinetics, and efficacy of LY3321367 (anti-TIM3) plus LY3300054 (Anti-PD-L1) and showed modest antitumor activity ( 173 ).…”
Section: Tim-3supporting
confidence: 73%
“…A phase I/II trial (NCT02608268) evaluated MGB453 (anti-TIM3) in combination with PDR001 (anti-PD-1) in advanced solid cancers such as melanoma and NSCLC and showed excellent safety profile and preliminary antitumor activity ( 170 ). Similar encouraging results were shown by trials (NCT02817633 and NCT03680508) that evaluated TSR-022 (anti-TIM3) in combination with PD-1 inhibitors ( 171 , 172 ). In addition, a phase Ia/b trial evaluated the safety, pharmacokinetics, and efficacy of LY3321367 (anti-TIM3) plus LY3300054 (Anti-PD-L1) and showed modest antitumor activity ( 173 ).…”
Section: Tim-3supporting
confidence: 73%
“…Similarly, different anti-TIM-3 mAbs combined with anti-PD-1 mAbs in the treatment of advanced lymphomas or NSCLC displayed higher efficacy than TIM-3 blockers alone (objective response rate (ORR): 42.9% vs. 0%; disease control rate (DCR): 42.9% vs. 11.1%) [ 167 ]. At the ASCO-SITC Clinical Immuno-Oncology Symposium of 2019, it was shown that in a Phase I a/b trial, the efficacy of LY3321367, an anti-TIM-3 mAb, in patients with NSCLC varied depending on the anti-PD-1/L1 efficacy; that is, the efficacy in anti-PD-1/L1 refractory patients ( N = 23, ORR: 0%, DCR: 35%, PFS: 1.9 months) was compared to that in anti-PD-1/L1 responders ( N = 14, ORR: 7%, DCR: 50%, PFS: 7.3 months).…”
Section: Clinical Trials Of Anti-lag-3 Anti-tim-3 and Anti-tigit Mabsmentioning
confidence: 99%
“…Combining GSK3359609 with pembrolizumab demonstrated promising anti‐tumor activity in patients with anti‐PD‐1/PD‐L1‐naïve HNSCC 135 . Furthermore, other co‐stimulator/co‐inhibitor targets, such as TIM‐3 and KIR, combined with anti‐PD‐1 therapy, are also being explored in various advanced solid tumors 136 . Personalized treatment approaches for HNSCC are focusing on targeting specific immune‐related pathways and combining various immunotherapies to increase anti‐tumor responses and provide a better patient outcome.…”
Section: Treatments In Personalized Medicinementioning
confidence: 99%